AGAMA DAN PEMBENTUKAN REALITAS DALAM PANDANGAN PETER LUDWIG BERGER - Rudy Harold (Universitas Kristen Satya Wacana, 2016)
This paper attempts to peer into the mind of Peter L.Berger in understanding the reality of religion. With the aim to obtain a description of sociological and theoretical fuller on how religion plays a role in the formation and preservation of the human world created for the benefit of the formation itself as being the